Time-varying formation control for unmanned aerial vehicles with external disturbances - Liu, Yu'ang (2021)
Time-varying formation control for unmanned aerial vehicles (UAVs) swarm systems with external disturbances is investigated via active disturbance rejection control (ADRC). The external disturbances are estimated by a designed extended state observer (ESO). Then, a distributed formation control protocol is designed according to the output of ESO, under which the predefined time-varying formation can be achieved. The closed-loop system under the proposed control strategy is analyzed. In addition, the expression of formation center function of the disturbed formation control is also depicted. Finally, numerical instances are simulated in order to demonstrate the validity and superiority of the proposed control strategy.